Transformasi Constitutional Review oleh Mahkamah Konstitusi dalam Negara Demokrasi Modern - Ady Supryadi; Rena Aminwara; Anies Prima Dewi; Tin Yuliani (Yayasan Pendidikan Kardin Assidiq, 2026)
The Constitutional Court (MK) has emerged as a pivotal institution within Indonesia's post-reform constitutional framework. Its establishment manifests the consolidation of constitutional supremacy and the checks and balances mechanism inherent in a modern democratic state. However, the evolution of constitutional review practices reveals a paradigm shift in the Court's role, transitioning from a mere negative legislator to increasingly acting as a positive legislator. This article aims to analyze the transformation of the MK's constitutional review authority within the context of modern democracy and evaluate its implications for Indonesia’s constitutional system. Employing a normative legal research method, this study utilizes statutory and conceptual approaches. The findings indicate that the transformation of the Court's authority is driven by the development of constitutional democracy, the imperative to protect citizens’ constitutional rights, and the necessity for national legal harmonization. Consequently, the study concludes that strict constitutional boundaries are imperative to prevent judicial overreach, which risks undermining the fundamental principle of the separation of powers.